Acute hemodynamic response to propranolol predicts bleeding and nonbleeding decompensation in patients with cirrhosis. Issue 9 (8th July 2022) - Hofer, Benedikt S.; Simbrunner, Benedikt; Bauer, David J. M.; Paternostro, Rafael; Schwabl, Philipp; Scheiner, Bernhard; Semmler, Georg; Hartl, Lukas; Jachs, Mathias; Datterl, Barbara; Staettermayer, Albert F.; Trauner, Michael; et al.
Abstract: Nonselective beta‐blockers are used as prophylaxis for variceal bleeding in patients with advanced chronic liver disease (ACLD). The acute hemodynamic response to intravenous propranolol (i.e., ≥10% reduction in hepatic venous pressure gradient [HVPG]) is linked to a decreased risk of variceal bleeding. In this study, we aimed to investigate the overall prognostic value of an acute response in compensated and decompensated ACLD. We analyzed the long‐term outcome of prospectively recruited patients with ACLD following a baseline HVPG measurement with an intraprocedural assessment of the acute hemodynamic response to propranolol. Overall, we included 98 patients with ACLD (mean ± SD age, 56.4 ± 11.5 years; 72.4% decompensated; 88.8% varices; mean ± SD HVPG, 19.9 ± 4.4 mm Hg) who were followed for a median of 9.6 (interquartile range, 6.5–18.2) months. Fifty‐seven patients (58.2%) demonstrated an acute hemodynamic response to propranolol that was associated with a decreased risk of variceal bleeding (at 12 months, 3.6% vs. 15% in nonresponder; log‐rank, p  = 0.038) and hepatic decompensation (at 12 months, 23% vs. 33% in nonresponder; log‐rank, p  = 0.096). On multivariate analysis, the acute response was an independent predictor of first/further hepatic decompensation (adjusted hazards ratio, 0.31; 95% confidence interval [CI], 0.13–0.70; p  = 0.005). Importantly, there was a tendency toward a prolonged transplant‐free survival in acute responders compared to nonresponders (34.2; 95% CI, 29.2–39.2 vs. 25.2; 95% CI, 19.8–30.6 months; log‐rank, p  = 0.191). Conclusions : Patients with ACLD who achieve an acute hemodynamic response to intravenous propranolol experience a lower risk of variceal bleeding and nonbleeding hepatic decompensation events compared to nonresponders. An assessment of the acute hemodynamic response to intravenous propranolol provides important prognostic information in ACLD. Abstract : While the acute haemodynamic response to intravenous propranolol has been linked to a reduced risk of variceal bleeding, its value in predicting first/further hepatic decompensation is unclear. In this study we observed that in addition to a decreased risk of variceal bleeding, patients with an acute haemodynamic response experienced a lower incidence of hepatic decompensation, which translated into a better survival. Thus, the acute response is a valuable prognostic tool that can be assessed in a single haemodynamic study, provides early risk stratification, and facilitates personalised therapy.image